The Structural Fate of Individual Multicomponent Metal‐Oxide Nanoparticles in Polymer Nanoreactors. (16th May 2017) - Du, Jingshan S.; Chen, Peng‐Cheng; Meckes, Brian; Xie, Zhuang; Zhu, Jinghan; Liu, Yuan; Dravid, Vinayak P.; Mirkin, Chad A.
Abstract: Multicomponent nanoparticles can be synthesized with either homogeneous or phase‐segregated architectures depending on the synthesis conditions and elements incorporated. To understand the parameters that determine their structural fate, multicomponent metal‐oxide nanoparticles consisting of combinations of Co, Ni, and Cu were synthesized by using scanning probe block copolymer lithography and characterized using correlated electron microscopy. These studies revealed that the miscibility, ratio of the metallic components, and the synthesis temperature determine the crystal structure and architecture of the nanoparticles. A Co‐Ni‐O system forms a rock salt structure largely owing to the miscibility of CoO and NiO, while Cu‐Ni‐O, which has large miscibility gaps, forms either homogeneous oxides, heterojunctions, or alloys depending on the annealing temperature and composition. Moreover, a higher‐ordered structure, Co‐Ni‐Cu‐O, was found to follow the behavior of lower ordered systems.